1992
DOI: 10.1056/nejm199209033271001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Captopril on Mortality and Morbidity in Patients with Left Ventricular Dysfunction after Myocardial Infarction

Abstract: In patients with asymptomatic left ventricular dysfunction after myocardial infarction, long-term administration of captopril was associated with an improvement in survival and reduced morbidity and mortality due to major cardiovascular events. These benefits were observed in patients who received thrombolytic therapy, aspirin, or beta-blockers, as well as those who did not, suggesting that treatment with captopril leads to additional improvement in outcome among selected survivors of myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
1,920
4
147

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 5,389 publications
(2,128 citation statements)
references
References 33 publications
26
1,920
4
147
Order By: Relevance
“…In mid‐1990s, the American Heart Association and the American College of Cardiology published the first clinical guidelines for heart failure (HF) 2, 3. Based in large part on the results of the SOLVD (Studies of Left Ventricular Dysfunction),4 SAVE (Survival and Ventricular Enlargement),5 CONSENSUS (Cooperative North Scandinavian Enalapril Survival Study),6 COPERNICUS (Carvedilol Prospective Randomized Cumulative Survival Study),7 MERIT‐HR (Metoprolol CR/XL Randomized Intervention Trial in Congestive Heart Failure),8 and CIBIS‐II (Cardiac Insufficiency Bisoprolol Study II)9 trials, HF guidelines have consistently focused on the benefits of neurohormonal therapy to delay progression and improve survival for patients with HF with reduced ejection fraction (HFrEF). More recent guidelines have also included emphasis on the importance of achieving and maintaining decongestion regardless of ejection fraction 10, 11, 12…”
Section: Introductionmentioning
confidence: 99%
“…In mid‐1990s, the American Heart Association and the American College of Cardiology published the first clinical guidelines for heart failure (HF) 2, 3. Based in large part on the results of the SOLVD (Studies of Left Ventricular Dysfunction),4 SAVE (Survival and Ventricular Enlargement),5 CONSENSUS (Cooperative North Scandinavian Enalapril Survival Study),6 COPERNICUS (Carvedilol Prospective Randomized Cumulative Survival Study),7 MERIT‐HR (Metoprolol CR/XL Randomized Intervention Trial in Congestive Heart Failure),8 and CIBIS‐II (Cardiac Insufficiency Bisoprolol Study II)9 trials, HF guidelines have consistently focused on the benefits of neurohormonal therapy to delay progression and improve survival for patients with HF with reduced ejection fraction (HFrEF). More recent guidelines have also included emphasis on the importance of achieving and maintaining decongestion regardless of ejection fraction 10, 11, 12…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin‐converting enzyme inhibitors (ACEi) and angiotensin II receptor blockers (ARB) have been shown in multiple large clinical trials to improve symptoms, reduce hospitalizations, and improve survival in patients with HF with reduced ejection fraction (HFrEF) 3, 4, 5, 6, 7. The American College of Cardiology (ACC)/American Heart Association (AHA) clinical guidelines make it a Class I, Level A recommendation to use ACEi/ARB therapy in patients with HFrEF both to “prevent symptomatic heart failure” and to “reduce morbidity and mortality.”8 In addition, the ACC/AHA HF Performance Measures recommend ACEi/ARB for outpatients with HFrEF and ACEi/ARB therapy at the time of hospital discharge for inpatients with HFrEF 9.…”
Section: Introductionmentioning
confidence: 99%
“…Similar mortality benefits were later demonstrated for captopril and ramipril in the Survival And Ventricular Enlargement Trial and The Acute Infarction Ramipril Efficacy Study trials in 1992 and 1993, respectively (Pfeffer et al ., 1992; The AIRE Study Group, 1993). In 1992, the Studies of Left Ventricular Dysfunction Prevention trial further demonstrated reduced HF incidence and cardiovascular mortality with enalapril, in patients with asymptomatic HFrEF (Cleland et al ., 2006).…”
Section: Evidence‐based Pharmacological Agentsmentioning
confidence: 99%